Механізм управління трудовим потенціалом суб’єктів економічних відносин - Власенко, Т. А.; Степаненко, С. В.; Левченко, А. В. (My University, 2021)
У статті було розроблено комплексний механізм управління трудовим потенціалом суб’єктів економічних відносин, де керуюча підсистема є множиною керівних посад та підрозділів, які впливають на реалізацію трудових функцій всіх підсистем підприємства, а керована система – множиною трудових функцій працівників всіх підрозділів і підсистем суб’єктів економічних відносин. Сам управлінський вплив об’єднує: принципи, функції та методи управління трудовим потенціалом та взаємодією механізмів мотивації та стимулювання персоналу, оцінювання ефективності використання трудового потенціалу та формування і використання інтелектуального та соціального капіталів. Реалізація управлінського впливу здійснюється шляхом декомпозиції HR-стратегії на відповідні тактики та конкретні заходи з її впровадження, що досягається за умови достатнього фінансового забезпечення, відповідного інформаційного забезпечення, включаючи елементи безпеки, дотримання вимог нормативно-правового забезпечення, а також існування на підприємстві дієвих регламентів його функціонування. The article developed a comprehensive mechanism for managing the labor potential of economic relations, where the management subsystem is a set of management positions and units that affect the implementation of labor functions of all subsystems of the enterprise, and the managed system - a set of labor functions of all units and subsystems economic relations. Management influence itself combines: principles, functions and methods of labor potential management and interaction of mechanisms of motivation and stimulation of personnel, evaluation of the effectiveness of labor potential and the formation and use of intellectual and social capital. Implementation of managerial influence is carried out by decomposing HR-strategy into appropriate tactics and specific measures for its implementation, which is achieved with sufficient financial support, appropriate information support, including security elements, compliance with regulatory requirements, as well as the existence of effective regulations. functioning. The concept of developing a mechanism for managing labor potential should be based on the initial provisions for understanding its nature and features of functioning. The nature of labor potential requires consideration of the levels of its formation and use from the nanoscale to the national and even global. The structure of the control mechanism must be formed by the control and managed subsystems, as they correspond to the cybernetic principle of operation of systems, the control system by implementing managerial influence tries to bring the controlled system to the desired state. The structure of managerial influence within the mechanism should cover a wide range of tools, among which traditionally consider the principles of management, functions, methods, types of support and internal mechanisms. The developed mechanism for managing the labor potential of economic relations involves the managerial influence of the control subsystem on the managed using a set of functionalities that combines the principles, functions, methods and management mechanisms that are formalized in HR-strategy, and ensuring their implementation is implemented through information, financial and regulatory component, including regulations for the operation of the enterprise. The process of making managerial decisions is an algorithm of actions that is implemented in the subsystems of personnel management, reflected in the mechanism of the functions divided into subjective and object components.
Mechanism of labor potential management of subjects of economic relations
Keywords: трудовий потенціал; механізм управління; декомпозиція HR-стратегії; інтелектуальний капітал; соціальний капітал; labor potential; management mechanism; decomposition of HR-strategy; intellectual capital; social capital